COVID-19 and the Endocrine System: A Review of the Current Information and Misinformation - Samir Ahmed Mirza; Abdul Ahad Ehsan Sheikh; Michaela Barbera; Zainab Ijaz; Muhammad Ali Javaid; Rahul Shekhar; Suman Pal; Abu Baker Sheikh (MDPI AG, 2022)
Coronavirus disease 2019 (COVID-19) infection primarily involves the respiratory system but has many noteworthy extra pulmonary manifestations as well. We write this review to highlight the basis of some pathophysiological mechanisms of COVID-19 infection-induced endocrine dysfunction. Different scientific databases and institutional websites were searched to collect and consolidate the most up-to-date data relating to COVID-19 infection and endocrine systems. Hypopituitarism, central diabetes insipidus, SIADH, thyroid abnormalities, hyperglycemia, adrenal insufficiency, orchitis and alteration in sperm morphology have been reported in case reports of patients with COVID-19 infection. Data focusing on COVID-19 vaccination was also searched to summarize the effect, if any, on the endocrine system. Endocrinopathies noted post COVID-19 vaccination, including cases of adrenal hemorrhage, new onset Type II Diabetes Mellitus and subacute thyroiditis, are also discussed in this review. This review calls attention to the misinformation relating to COVID-19 vaccination with supposed endocrine effects such as infertility and problems with pregnancy. Rebutting these misconceptions can help increase compliance and maximize COVID-19 vaccination to the public.